PENERAPAN VIDEO TUTORIAL SULAM PAYET PADA ELEMEN DESAIN HIASAN DI KELAS XI TATA BUSANA SMK DHARMA WANITA GRESIK - Putri, Shendy Mutiara Anjani; Rahayu, Imami Arum Tri; Arifiana, Deny; Mayasari, Peppy (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2023)
The background to this research is the lack of attention of students during learning, the learning process uses lecture and demonstration methods. The media used are sequin embroidery fragments and ppt. School facilities are not utilized optimally during learning. Students tend to be bored and less motivated to explore the material. The purpose of this research is to determine the implementation of learning to make sequin embroidery using video tutorial media, to find out student learning outcomes on sequin embroidery material, student responses to the application of video tutorial media for making sequin embroidery. This type of research uses pre-experiments with a One Shoot Case Study pattern. The results of implementing learning using video tutorial media obtained a score of 88%, which is in the very good category. Student learning outcomes using video tutorial media were declared complete Criteria for Achieving Learning Objectives with a class average of 83.5% and a classical average of 91.6%. The student response questionnaire obtained 90.8%, including the very good category. The findings of this research are able to help students understand the material so that they achieve completeness with a score beyond the Criteria for Achieving Learning Objectives.